PENGARUH KUALITAS PELAYANAN DAN CITRA TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN NASABAH BANK BRI CABANG CAWANG - Leo Frits Dharmadi; Bernadin Dwi M. (Ekonomi dan Bisnis, 2015)
Bank BRI in 1946 first established as a government-owned bank first and then in 1992 legal entities BRI transformed into Limited Liability Company. In 2003 ownership pemerintas sale so this status as a public company, later changed its name to PT. Bank Rakyat Indonesia (Persero) Tbk. This study was conducted to test the analysis Influence of Service Quality And Customer Loyalty Through Imagery Customer Satisfaction Customer Bank BRI. The population in this study of 100 respondents who use the services of Bank BRI Branch Cawang. Data obtained from questionnaires distributed at Bank BRI branch Cawang. The sample used in this study were 100 respondents who use the services of data BRI. Sampling technique using purposive sampling method. Analysis technique used is the analysis of lane or path analysis. These results indicate that significant influence service quality directly to customer satisfaction, significant bepengaruh image directly to customer satisfaction, quality of service and the image of the significant influence indirectly through customer satisfaction to customer loyalty and customer satisfaction directly significant effect on customer loyalty.